THE INFLUENCE OF AL-5TI-1B AND AL-10SR ON MICROSTRUCTURAL EVOLUTION AND MECHANICAL PROPERTIES OF HYPOEUTECTIC ALUMINUM-SILICON ALLOY - Archardy Antory, Benedito
This study investigates the microstructural evolution and mechanical properties of hypoeutectic aluminum-silicon (Al-Si) alloy subjected to grain modification and eutectic modification treatments. Three objectives were pursued: to evaluate the effect of Al-5Ti-1B as grain modifier, to assess the influence of Al-10Sr as modifier, and to analyze the combined effect of both treatments on the alloy's microstructure and mechanical behavior. In summary, the methodology involved the addition of 0.5 wt% of each master alloy to the molten Al-Si alloy, followed by tensile testing and microscopic examination. The findings reveal distinct effects of the treatments on the alloy properties. The addition of Al-5Ti-1B resulted in larger secondary dendrite arm spacing (SDAS), enhancing the strength and its ductility, also with the increasing fraction of ?-Al phase. Conversely, Al-10Sr modification led to a decrease in strength but an improvement in ductility, accompanied by a transformation of silicon morphology from plate-like to globular, termed as "coral-like" eutectic. It was also observed that the fraction of the eutectic phase also increased. Interestingly, the combined effect of Al-5Ti-1B and Al-10Sr led to a dominance of the strontium's effects on both mechanical behavior and microstructural changes.